Potential of Metschnikowia yeasts in green applications: a review - Liu, Jiayue; Rygała, Anna; Zhang, Bolin; Kręgiel, Dorota (Frontiers in Microbiology, 2025)
The unconventional yeasts Metschnikowia spp. represent a valuable microorganisms with enormous yet untapped potential. Metschnikowia species are briefly reviewed, demonstrating that taxonomic and genomic analysis can open numerous opportunities to exploit their unique character and potential in the development of modern winemaking and brewing, probiotics and biocontrol, and the synthesis of single-cell proteins. These yeasts can be used in both bioprocesses and biorefineries, contributing to the production of biofuels and unique products recovered from agro-industrial wastes. This review, through a comprehensive bibliographic analysis, examines various green strategies for the production of alcohols, lipids, unsaturated fatty acids, and other valuable metabolites. Furthermore, the article discusses the challenges and barriers hindering the full implementation of Metschnikowia spp. in new approaches and technologies.